AKTIVITAS ANTIOKSIDAN DAN KEMAMPUAN ANTIBAKTERI EKSTRAK KULIT BUAH KENITU (Chrysophyllum cainito L) TERHADAP Staphylococcus aureus - Rahayu, Lina Oktavia (Jurnal Penelitian Farmasi & Herbal, 2023)
Kenitu (Chrysophyllum cainito L) has strong antioxidant properties both in vitro and in vivo. The presence of this high antioxidant can be used as a natural agent to prevent and treat diseases associated with an imbalance of antioxidant levels in the body, such as diabetes. Some research results state that kenitu can be used as an antidiabetic. One type of complication in people with diabetes mellitus is the occurrence of bacterial infections of the skin. One type of bacteria that infects the most is Staphylococcus aureus. So far, the skin of the kenitu fruit has only been thrown away and has not been used. The purpose of this study was to determine the antioxidant activity of kenitu peel extract and to determine the ability of kenitu peel extract as an antibacterial against Staphylococcus aureus. Research methods included extracting kenitu peel by maceration using 70% ethanol, testing antioxidant activity using the DPPH method, and testing the antibacterial activity of kenitu peel extract against Staphylococcus aureus. The results of the antioxidant activity test showed an IC50 value of 126.96 ppm. Antibacterial activity testing showed a MIC value of 250 ppm and a MBC value of 500 ppm. The conclusion of this study is that kenitu peel extract has moderate antioxidant activity and kenitu peel extract is able to inhibit the growth and kill Staphylococcus aureus bacteria.